INTELLECTUAL CAPITAL MANAGEMENT UNTUK REVITALISASI IMPLEMENTASI E-GOVERNMENT DI INDONESIA - Azida Batubara, Noor (Pusat Pengembangan Sumber Daya Manusia Aparatur, 2020)
The purpose of this research is to identify the factors influencing implementation of e-government in Indonesia, using the perspective of Intellectual Capital Management. The low ranking of Indonesia's egovernment implementation based on data released by the United Nations, is internally institutional, due to the lack of human resources knowledge of e-government. While, externally institutional factor is causedby low public awareness of the importance of e-literacy, and other factors that affect the quality of egovernment implementation in Indonesia. A management system is needed that can boost e-government implementation better. Methodology of this research is used a descriptive qualitative approach, data that support research is obtained through the study of literature sourced from relevant books, scientificjournals, scientific articles, and the internet that are relevant to the application of Intellectual Capital Management in order to produce in-depth and comprehensive information, regarding related issues. The result of research showed, that three capitals of ICM that they enggage and support each other in knowledge eternally (human capital, structural capital, and relational capital) is a concept of institutional management with its projected value creation, through knowledge and innovation. It can to increase quality of superior and innovative e-government that contributes to the nation and state of Indonesia positively. ABSTRAKTujuan penelitian ini adalah untuk mengidentifikasi faktor-faktor yang berpengaruh terhadap implementasi e-government di Indonesia menggunakan perspektif Intellectual Capital Management. Rendahnya peringkat implementasi e-government Indonesia berdasarkan data yang dirilis oleh PBB, secara internal kelembagaan, disebabkan masih minimnya pengetahuan SDM terhadap e-government.Adapun secara eksternal kelembagaan disebabkan rendahnya kesadaran masyarakat terhadap pentingnya melek e-literacy, dan faktor-faktor lainnya yang mempengaruhi kualitas implementasi e-government di Indonesia. Diperlukan sebuah sistem manajemen yang dapat mendongkrak terimpelemntasikannya egovernmentdengan lebih baik. Menggunakan metode penelitian dengan pendekatan kualitatif deskriptif, data-data yang mendukung penelitian diperoleh melalui studi literatur kepustakaan yang bersumber dari buku-buku yang relevan, jurnal ilmiah, artikel-artikel ilmiah, dan internet yang relevan dengan penerapan Intellectual Capital Management guna menghasilkan informasi yang mendalam dan komprehensifmengenai permasalahan terkait. Hasil penelitian menunjukkan ICM dengan ketiga elemennya yang saling bersinergi melalui pengetahuan (human capital, structural capital, dan relational capital) merupakan konsep manajemen lembaga dengan proyeksi penciptaan nilai melalui pengetahuan dan inovasi yang dimilikinya dapat meningkatkan kualitas e-government yang unggul dan inovatif yang berkontribusipositif bagi bangsa dan negara Indonesia.